Patient experiences of rehabilitation following traumatic complex musculoskeletal injury – A mixed methods pilot study. (July 2022) - Silvester, LA; Trompeter, AJ; Hing, CB
Introduction: The aim of this pilot study was to measure patient reported outcomes and evaluate their rehabilitation experience following traumatic complex musculoskeletal (CMSK) injury. Methods: A mixed methods prospective observational study was undertaken between December 2015 and March 2018 to explore patient reported outcomes following CMSK injury sustained as a result of major trauma and perception of their rehabilitation and its impact on their recovery. The participants were asked to complete a series of outcome measures at 18-months post-injury. The data was anonymised and analysed by the lead researcher. Results: Thirty patients were recruited into the study (19 males, 11 females) between 23 and 76 years of age (median 52 years). Their injury profile was split between open fractures 30%, pelvic fractures 23%, multiple fractures 27% and polytrauma 20%. The majority (60%) reported moderate disability at 18-months post injury with 50% returning to full time employment. Patients with multiple or open fractures reported the worst outcomes. There was no relationship between frequency, quantity or duration of physiotherapy and outcome. However, 77% reported supplementing their NHS rehabilitation with other interventions such as gym membership, hydrotherapy and psychological therapies. The thematic analysis showed that patients considered intensity, quality and coordinated timely access to rehabilitation as the most important factors. Conclusion: From a patient perspective, the current NHS rehabilitation provision does not appear to meet their complex needs. In addition to physical and vocational rehabilitation, patients wanted effective pain management and psychological support. Strengthening current therapy services and involving other sectors (e.g. Citizen's Advice) could help achieve this. Early access to an intensive multidisciplinary rehabilitation programme was perceived to have positive benefits and improve outcomes.